2020
DOI: 10.1002/ejic.201901177
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Azo‐ and Imino‐Based Carboxylate Triphenyltin(IV) Compounds

Abstract: Azo (‐N=N‐)‐ and imino (‐C=N‐)‐carboxylate triphenyltin(IV) compounds, which are well known for their promising biological activities, are usually synthesized by reacting a triphenyltin(IV) compound (oxide, hydroxide or chloride) with a suitably substituted carboxylic acid, under appropriate conditions. Their biological properties are influenced by the type/position of the functional azo or imino group in the carboxylate ligand skeleton. They are very effective in anticancer studies, being often better than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It was proved that the introduction of a hydroxyimino group at C3 of the oleanan could affect the inhibition of tumor cell proliferation, and additionally cause cell death by apoptosis, autophagy, or necrosis [ 65 ]. However, it was reported that the imino group might have diverse biological activities, including antimicrobial activity, antiviral activity, and most importantly, antitumor activity [ 66 ]. It is also known that a hydrogen NHOH group may form a weak hydrogen bond with the oxygen atom of the keto- group, and the whole structure of the molecule acquires greater lipophilicity, which allows for easier penetration of the compound into the cell structures [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the introduction of a hydroxyimino group at C3 of the oleanan could affect the inhibition of tumor cell proliferation, and additionally cause cell death by apoptosis, autophagy, or necrosis [ 65 ]. However, it was reported that the imino group might have diverse biological activities, including antimicrobial activity, antiviral activity, and most importantly, antitumor activity [ 66 ]. It is also known that a hydrogen NHOH group may form a weak hydrogen bond with the oxygen atom of the keto- group, and the whole structure of the molecule acquires greater lipophilicity, which allows for easier penetration of the compound into the cell structures [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the anticancer activities previously reported for organotin (IV) complexes, we performed cell viability studies on the obtained compounds 1 and 2. 47,48 The MTT assay was performed with two cancer cell lines (human lung cell lines, A549 and rat basophilic leukemia cells, RBL) using a control (0.1% DMSO). Images and results are shown in Figures 3 and S10.…”
Section: In Vitro Cytotoxicity Against A549 and Rbl Cancer Cells: Mtt...mentioning
confidence: 99%
“…9–17 This has prompted significant research efforts towards the design of organotin( iv ) complexes as potential anticancer agents, aiming to enhance their therapeutic efficacy through selective cytotoxicity against cancer cells. 11–18…”
Section: Introductionmentioning
confidence: 99%